PEMANFAATAN BIOTEKNOLOGI DALAM PEMBUATAN TAPE KETAN SEBAGAI PRODUK UNGGULAN LOKAL - Syahrir, Maulidyah; Wahyuddin, Munifah; Muh. Yasid Alim; Fauzia Amelia; A. Aulia Maulidha; Dhela Fitria (Akademi Farmasi Yamasi Makassar, 2024)
Black sticky rice contains phenolic components which have antioxidant properties, and sticky rice tape is a traditional fermented product that is rich in cultural value in Indonesia. The process of making sticky rice tape, which involves fermentation by microorganisms such as yeast, can be optimized through the application of biotechnology to improve the quality, stability and economic value of the product. Conventional, non-standardized production methods often result in varying tape quality. Therefore, this community service program aims to provide knowledge and skills to the community in applying simple biotechnology in the production of sticky rice tape. Through training, people can understand the principles of fermentation and develop new product variations. The results of this program show an increase in the quality of the sticky rice tape produced, including better taste, texture and shelf life. Product diversification and the use of modern marketing techniques also increase the competitiveness of sticky rice tape in the market. Overall, this program has a positive impact on increasing income and economic welfare of local communities. Keywords: tape, fermentation, biotechnology, product, local